Падение объемов промышленного производства в Украине и пути выхода из кризиса - Сикетина, Наталья Геннадиевна; Клочко, Юрий Александрович; Камчатная-Степанова, Екатерина Валерьевна (НТУ "ХПІ", 2015)
В статье рассматривается снижение темпов промышленного производства в Украине. Проведен анализ данных о состоянии промышленности на сегодняшний день в сравнении с 2013 годом. Последствия войны на Юго-Востоке Украины и конфликта двух крупных компаний российского «Газпромом» и украинского «Нафтогаз». Сделаны выводы о необходимости привлечения иностранных инвесторов для увеличения доходов от загрузки промышленного производства.

The article considers decline in industrial production in Ukraine. The tendency of decline of industrial production volume is analysed, to what a price increase is related on the prepared home products and increase of unemployment in a country. Analyzed state data industry now compared with 2013 year. Consequences of the war in the south-east of Ukraine and the conflict of two major companies in the Russian Gazprom and Ukrainian Naftogaz. And to propose ways out of the crisis.Such as to count a living wage on one man in a month at the new course of hryvnia in relation to a dollar or euro; to begin to lift agriculture; in parallel it is needed to start enterprises on processing of wastes; it is needed to lift heavy industry due to major concerns. It is also necessary to attract specialists, investors for the increase of profits from loading of industrial production. It will help, on some time, to replace the loss of industrial production and decrease the indexes of unemployment. Conclusions about the need to attract foreign investors to increase revenue from downloading of industrial production was made.
Falling volumes of industrial production in Ukraine and ways out of the crisis
Keywords: кризисная среда; сбыт продукции; загрузка производства; иностранные инвесторы; industrial production; crisis environment; product sales; download production